1973
DOI: 10.1136/ard.32.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and scanning study of patients receiving intra-articular injections of gold-198 and yttrium-90.

Abstract: An account of the chromosome damage found in the lymphocytes of thirteen patients who had received injections of gold-198 into knee joints was reported in a preliminary communication (Stevenson, Bedford, Hill, and Hill, 1971a). There were great differences in the amount of damage which followed injections of the same amount of activity in these patients. However, the mean level of damage appeared too high to be explained by the assumption either that it occurred as a result of irradiation of lymphocytes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The concerns are mostly based on observed chromosomal abnormalities in peripheral lymphocytes after radiosynovectomy. [6][7][8][9] However, the latency period before development of a cancer lasts for years in the case of small doses of radiation. Risk of leukaemia is estimated to be greatest 5-10 years after the exposure, whereas the risk of solid tumours increases during the rest of the lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concerns are mostly based on observed chromosomal abnormalities in peripheral lymphocytes after radiosynovectomy. [6][7][8][9] However, the latency period before development of a cancer lasts for years in the case of small doses of radiation. Risk of leukaemia is estimated to be greatest 5-10 years after the exposure, whereas the risk of solid tumours increases during the rest of the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities have been found in peripheral lymphocytes after radiosynovectomy. [6][7][8][9] The clinical significance of these changes remains unknown. To our knowledge, no studies of the incidence of cancer in patients who have received intra-articular yttrium injections have been reported.…”
mentioning
confidence: 99%
“…The correlation observed between dicentrics and the concentration of tritium in the urine samples of workers is almost identical with the correlation of dicentrics and the duration of occupational exposure ( 0X82, `0X001 and 0X81, `0X001, respectively). As the half-life of peripheral blood lymphocytes is estimated to be approximately 3 years [17,34], the accumulation of exchange aberrations in peripheral blood lymphocytes in a dose-related manner would be expected. Since Spruill et al [33] have recently demonstrated that the half-life of lymphocytes carrying lethal chromosome damage is much lower than 3 years, the incidence of dicentrics obtained in the present study is due to the concentration of tritium in urine rather than to the duration of occupational exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Dvoreckij et al, 1971;Brewen et al, 1972;Pjatkin, 1976 , Ž in patients undergoing radiotherapy Tamura et al, 1970;Pyatkin et al, 1972b;Schmid et al, 1974a;Silberstein et al, 1974;Chee and Ilbery, 1975;Watson andGillies, . Ž 1975 or therapy with radionuclides Arbor, 1964;Cantolino et al, 1966;De la Chapelle et al, 1972;Stevenson et al, 1973;Blackwell et al, 1974;Boyd et al, 1974; . Lloyd et al, 1976 .…”
Section: ( ) Deõelopment and Standardization Of The Dicentric Dic Assaymentioning
confidence: 99%